Synthesis, Spectroscopic, and Characterization of Novel Nano Sized Mannich Base Complexes with Pt (IV) and Au (III) Ions and Assessing Their Antioxidants Activity - Alya'a J. Ahmed; Mahasin F. Alias (مجلة بغداد للعلوم)
This study focuses on the synthesis of nano pt(IV) and Au(III) Mannich base complexes derived from ciprofloxacin by the ultrasonic sonication method. The size and morphology of nanocomplex were measured by transmission electron microscopy (TEM), atomic force microscopy (AFM), energy dispersive X-ray (EDX), scanning electron microscopy (SEM), x-ray differentiation (XRD) and Fourier transform infrared spectroscopy (FTIR). Newly synthesized ligand and their metal complexes were tested for their ability to scavenge free radicals at concentrations between 6.25 and 100 µg/ml using their interaction with the stable free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH). It has been demonstrated that all compounds enhance antioxidant activity in high concentration.